The risks and challenges faced by workers in the face of the use of artificial intelligence at work - Torres Cadillo, Rosa Isabel (2023)
The use of artificial intelligence at work presents both risks and challenges for workers. On the one hand, risks can include job losses due to automation, lack of protection of personal data, and potential discrimination in candidate selection. On the other hand, challenges may include the need for constant adaptation and training to work with advanced technology, as well as ensuring that decisions made by artificial intelligence are fair and ethical. It is therefore important that measures are taken to protect labor rights and ensure a just transition towards an increasingly automated work environment.